Contingent Capital Solution: Integrating Capital Management into Risk Management - Luong, Thi Thanh Huyen (2006)
This dissertation studies a risk management approach which integrates capital management into risk management by enabling post-loss capital issuance at pre-loss terms, the contingent capital approach. This new approach is examined following an evaluation framework used in studying the value of risk management. The analytical evaluation suggests that using contingent capital brings in benefits in mitigating underinvestment problem and reducing cost of issuing capital, but its impact on tax liabilities, agency conflict, and costs of financial distress might not result in value enhancement as the theory predicted. It is therefore advisable that firms take into account various effects of different risk management approaches, especially those involving integration of different corporate functions, to make appropriate decisions for their risk management programs.